Association between Diabetes Mellitus and Tuberculosis in United States-Born and Foreign-Born Populations in San Francisco - Suwanpimolkul, Gompol; Grinsdale, Jennifer A.; Jarlsberg, Leah G.; Higashi, Julie; Osmond, Dennis H.; Hopewell, Philip C.; Kato-Maeda, Midori (PloS one, 2014)
The impact of diabetes on tuberculosis in United States and foreign-born populations in San Francisco has not been studied. To determine the characteristics, prevalence and temporal trends of diabetes in US and foreign-born persons attending the San Francisco Tuberculosis Clinic. We analyzed data from individuals seeking medical attention at the San Francisco Tuberculosis Clinic. We included patients with diagnosis of tuberculosis, latent infection, or not infected with Mycobacterium tuberculosis. We assessed the temporal trend and the characteristics of individuals with and without diabetes. Between 2005 and 2012, there were 4371 (19.0%) individuals without evidence of tuberculosis infection, 17,856 (77.6%) with latent tuberculosis, and 791 (3.4%) with tuberculosis. 66% were born in the United States, China, Mexico, and the Philippines. The prevalence of diabetes was the highest among individuals with tuberculosis and increased during the study period. Patients with tuberculosis and diabetes were more likely to be male, older than 45 years and born in the Philippines. There was a disproportionate association of TB and DM relative to LTBI and DM among Filipinos in individuals older than 45 years old. Our data suggest that Filipinos older than 45 years old are more likely to have tuberculosis probably due to a higher prevalence of diabetes. In San Francisco, tuberculosis-screening programs in individuals with diabetes and latent tuberculosis may be beneficial in patients older than 45 years old especially from the Philippines.